2009
DOI: 10.1097/grf.0b013e3181c11edf
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in Pregnancy

Abstract: In the United States, trauma is the leading nonobstetric cause of maternal death. The principal causes of trauma in pregnancy include motor vehicle accidents, falls, assaults, homicides, domestic violence, and penetrating wounds. The managing team evaluating and coordinating the care of the pregnant trauma patient should be multidisciplinary so that it is able to understand the physiologic changes in pregnancy. Blunt trauma to the abdomen increases the risk of placental abruption. Evaluation of the pregnant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 21 publications
(72 reference statements)
2
82
0
7
Order By: Relevance
“…[3][4][5][6] Further, several non-population-based US studies have shown that blunt physical trauma, the majority of which are attributed to MVA, is the leading cause of non-obstetrical maternal mortality. 1,3,7,8 Moreover, motor vehicle crashes represent an important cause of perinatal mortality with an incidence of fetal/neonatal death at 3.7 per 100 000 pregnancies, attributable in large part to placental abruption and uterine rupture. 9 Despite the potentially significant and life-threatening implications for mother and baby, there is a paucity of data available regarding maternal injuries and outcomes in pregnant women having had an MVA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Further, several non-population-based US studies have shown that blunt physical trauma, the majority of which are attributed to MVA, is the leading cause of non-obstetrical maternal mortality. 1,3,7,8 Moreover, motor vehicle crashes represent an important cause of perinatal mortality with an incidence of fetal/neonatal death at 3.7 per 100 000 pregnancies, attributable in large part to placental abruption and uterine rupture. 9 Despite the potentially significant and life-threatening implications for mother and baby, there is a paucity of data available regarding maternal injuries and outcomes in pregnant women having had an MVA.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma, including suicide, accidental injury, motor traffic accidents, and homicides, is the leading nonobstetric cause of late maternal death in the United States [10] and accounted for 73% of all maternal deaths (early and late) in NSW over an eight-year study period [3]. These nonmedical deaths, and most notably, the late maternal deaths, are underreported [11] and are not as well documented or acknowledged as the obstetric causes listed above.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty-two percent of fetal deaths occur from motor vehicle accidents (MVA). Other causes of fetal death from maternal trauma occur because of gunshot wounds (6%), falls (3%), and maternal death (11%) [28].…”
Section: Introductionmentioning
confidence: 99%